PENGARUH KOMPRES HANGAT DENGAN BOTOL KACA TERHADAP PENURUNAN NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS KLATEN SELATAN - Savitri, Indah; Satiyem, Satiyem; Sumantri, Sumantri (Jurnal Kebidanan, 2024)
Back pain is the most common complaint with a prevalence rate of 49%. About 80-90% of pregnant women who experience back pain state that they do not make any efforts to overcome the symptoms, in other words only around 10-20% of them do medical care to health workers. One treatment is non-pharmacological therapy with warm compresses which can provide a feeling of comfort. The hot feeling caused by warm compresses can result in vasodilation, namely the blood vessels widen and improve blood flow so that the muscles become more relaxed. This type of quantitative research is a quasi-experimental design with a serial one-group pretest and posttest design. The total sampling data collection technique was obtained. The data analysis used parametric statistics because the data is normally distributed using Paired T-Test with a significant level of <0.05. The reduction in the intensity of low back pain during the first intervention (post test 1) was an average of 5.514, after the second intervention (post test 2) the average was 4.511, and after the third intervention (post test 3) the average was 3.425. And the most significant decrease was in the second intervention with a t value of 27.499. Here is a significant effect on reducing lower back pain in third trimester pregnant women in both the first, second and third interventions with a p value of 0.000 (p <0.005). However, the most significant effect was on the second intervention with a t value of 27.499.